2006
DOI: 10.1111/j.1540-8191.2006.00265.x
|View full text |Cite
|
Sign up to set email alerts
|

Atrial Myxomas: Pathologic Types, Tumor Location, and Presenting Symptoms

Abstract: CHF was more common with solid myxomas, and neurologic and embolization events were more common in the papillary type. Septal tumor location showed strong association with CHF, while extraseptal location correlated with neurologic events. We speculate that the various gross and microscopic patterns reflect secondary changes within these neoplasms over the course of their natural history.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
58
1
6

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(68 citation statements)
references
References 27 publications
3
58
1
6
Order By: Relevance
“…Although most LA myxomas are attached to the LA septum, Swartz et al reported that an extraseptal location was correlated with embolic events (13). It is also useful to assess the risk of embolism with findings on CAG.…”
Section: Discussionmentioning
confidence: 99%
“…Although most LA myxomas are attached to the LA septum, Swartz et al reported that an extraseptal location was correlated with embolic events (13). It is also useful to assess the risk of embolism with findings on CAG.…”
Section: Discussionmentioning
confidence: 99%
“…5) By contrast, peripheral embolism as an initial manifestation is not very common at 13%. 1) If we meet a case with arterial thrombosis or occlusion, transthoracic echocardiography is a mandatory basic evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…As another source of embolisation papillary myxomas often contain superficial blood clots and hemorrhagic foci embedded among their villous extension. Contrary, in polypoid tumors hemorrhagic foci are more frequently internalize [105].…”
Section: Recurrence and Malignant Potential Of Cardiac Myxomamentioning
confidence: 99%